2017
DOI: 10.4172/jpb.1000452
|View full text |Cite
|
Sign up to set email alerts
|

The Cortisol Steroid Levels as a Determinant of Health Status in Animals

Abstract: The veterinarian is daily faced with the challenge of diagnosing several disease conditions in different animals. Quantifying cortisol levels has been used in the evaluation of anxiety and distress initiated by infectious and noninfectious disease conditions, mismanagement, transportation, adverse environmental temperature and surgical operations. The hormone-cortisol has been implicated in several immunologic and metabolic processes and can thus serve as a marker to monitor animal welfare. Several factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This result was similar to the previous study in the dairy cows which showed the plasma cortisol concentration of noncooled cow tended to be higher than that of the cows housed in a close-sided barn under an evaporative cooling system (Chaiyabutr et al, 2008). During stress, the hypothalamic-pituitary adrenal axis (HPA) is stimulated and synthesis of adrenocorticotrophic hormone (ACTH) by the anterior pituitary (Kannan et al, 2000;Saidu et al, 2016;Isaac et al, 2017). Therefore, increasing plasma cortisol concentration during the afternoon from both seasons in the present study supposedly related to the stress response of HTa effect of the goats.…”
Section: Stress Status In Saanen Goatsupporting
confidence: 89%
See 1 more Smart Citation
“…This result was similar to the previous study in the dairy cows which showed the plasma cortisol concentration of noncooled cow tended to be higher than that of the cows housed in a close-sided barn under an evaporative cooling system (Chaiyabutr et al, 2008). During stress, the hypothalamic-pituitary adrenal axis (HPA) is stimulated and synthesis of adrenocorticotrophic hormone (ACTH) by the anterior pituitary (Kannan et al, 2000;Saidu et al, 2016;Isaac et al, 2017). Therefore, increasing plasma cortisol concentration during the afternoon from both seasons in the present study supposedly related to the stress response of HTa effect of the goats.…”
Section: Stress Status In Saanen Goatsupporting
confidence: 89%
“…The secondly and thirdly levels are the mild degree or reversible heat stress and severe degree or irreversible heat stroke, respectively. These two levels of heat stress risen together with increasing plasma cortisol (Isaac et al, 2017). Since RR, plasma GPx activity, and plasma cortisol from both winter and summer were increased significantly during the afternoon, this suggested that the goats from both winter and summer groups were mild degree of heat stress.…”
Section: Stress Status In Saanen Goatmentioning
confidence: 96%
“…Chronic stress in animals such as poor housing (lairage) condition, starvation/malnutrition and perpetual fear/anxiety due to sights of cruelty and painful killing can inhibit the activities of lymphoid tissues resulting in low immune-cells counts (leucocytopenia), particularly the T-lymphocytes [71][72][73][74][75][76]. Both physicochemical and psychological types of stress in FPAs may lead to persistent high levels of serum cortisol and corticosteroid, causing increased vulnerability to infectious diseases [77][78][79][80]. Exposure of FPAs to stress may also impair the anti-inflammatory functions of the immune system and inhibit the cross-talk of immune cells and signalling networks; resulting in increased susceptibility to infections and diseases; which may be zoonotic or contagious to other animals [81][82][83].…”
Section: Plos Onementioning
confidence: 99%
“…Assessing animal health and disease is traditionally determined through clinical evaluation by a qualified individual, which is often a veterinarian [68]. For instance, cortisol, a hormone associated with stress, is usually detected through the saliva or blood of animals, using hormone extraction and quantification methods such as radioimmunoassay [69]. Similarly, diagnosing diseases, such as chlamydia in koalas (Phascolarctos cinereus), often involves collecting a sample from the affected area on the animal for antigen, antibody, DNA, or microbial testing [70].…”
Section: Animal Health and Diseasementioning
confidence: 99%